Neoadjuvant ipilimumab plus nivolumab in synchronous clinical stage III melanoma. (May 2021) - Versluis, Judith M.; Reijers, Irene L.M.; Rozeman, Elisa A.; Menzies, Alexander M.; van Akkooi, Alexander C.J.; Wouters, Michel W.; Ch'ng, Sydney; Saw, Robyn P.M.; Scolyer, Richard A.; van de Wiel, Bart A.; Schilling, Bastian; Long, Georgina V.; et al.
Abstract: Background: Patients with synchronous clinical stage III melanoma can present with primary melanoma lesions, locally recurrent melanoma or in-transit metastases. Neoadjuvant ipilimumab plus nivolumab induces high pathologic response rates and an impressive relapse-free survival in patients with nodal macroscopic stage III melanoma. Whether primary site melanoma and in-transit metastases respond similarly to lymph node metastases with neoadjuvant immunotherapy is largely unknown. Such data would clarify whether surgical excision of these melanoma lesions should be performed before neoadjuvant therapy or whether it could be deferred and performed in conjunction with lymphadenectomy following neoadjuvant immunotherapy. Patients: Patients with synchronous clinical stage III melanoma were identified from the OpACIN, OpACIN-neo and PRADO neoadjuvant trials, where all patients were treated with ipilimumab plus nivolumab. An additional case treated outside those clinical trials was included. Results: Seven patients were identified; six patients had a concordant response in primary site melanoma lesions or in-transit metastasis and the lymph node metastases. One patient had concordant progression in both the primary and nodal tumour lesions and developed stage IV disease during neoadjuvant treatment, and thus, no resection was performed. Conclusion: Pathologic response following neoadjuvant ipilimumab plus nivolumab in primary site melanoma lesions or in-transit metastasis is concordant with a response in the lymph node metastases, indicating that there may be no need to perform upfront surgery to these melanoma lesions prior to neoadjuvant treatment. Highlights: Response to neoadjuvant therapy is concordant in the primary site and nodal melanoma. Neoadjuvant therapy induces high response rates in the primary site and nodal melanoma. Consider postponing resection of the primary site melanoma to after neoadjuvant therapy.